2020
DOI: 10.1002/ange.202003688
|View full text |Cite
|
Sign up to set email alerts
|

Does a Thermoneutral Electrocatalyst Correspond to the Apex of a Volcano Plot for a Simple Two‐Electron Process?

Abstract: Volcano analyses have been established as a standard tool in the field of electrocatalysis for assessing the performance of electrodes in a class of materials. The apex of the volcano curve, where the most active electrocatalysts are situated, is commonly defined by a hypothetical ideal material that binds its reaction intermediates thermoneutrally at zero overpotential, in accordance with Sabatier's principle. However, recent studies report a right shift of the apex in a volcano curve, in which the most activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…This strategy was pursued, among others, by Zhong and Li, reporting that an increased coordination number of the active metal center results in an improved oxygen reduction activity for fuel cell catalysis. 55 In conclusion, the breaking of the volcano-shaped curve by tuning the drug coordination number in Figure 4 reveals similarities with the discussion of volcano plots and their limitations in catalysis, 56,57 where the design of multifunctional active sites with adjustable coordination number and adjustable covalence/solution contributions appears expedient to surmount inherent boundaries given by the volcano curve.…”
Section: Resultssupporting
confidence: 66%
“…This strategy was pursued, among others, by Zhong and Li, reporting that an increased coordination number of the active metal center results in an improved oxygen reduction activity for fuel cell catalysis. 55 In conclusion, the breaking of the volcano-shaped curve by tuning the drug coordination number in Figure 4 reveals similarities with the discussion of volcano plots and their limitations in catalysis, 56,57 where the design of multifunctional active sites with adjustable coordination number and adjustable covalence/solution contributions appears expedient to surmount inherent boundaries given by the volcano curve.…”
Section: Resultssupporting
confidence: 66%
“…Because this information is not known a priori , caution should be practiced in applying this assumption. For example, the inclusion of applied potential and kinetics to the model developed by Exner showed that volcano plots describing the activity of electrocatalysts toward the HER shifted such that electrocatalysts with endergonic binding of hydrogen, as opposed to thermoneutral adsorption, are predicted to have optimal HER activity . In another recent example, Dickens et al calculated electrochemical OER activation barriers and reaction energetics under an applied potential, resulting in an OER volcano plot that is a function of the current density, as opposed to thermodynamic, limiting-potential volcano plots that are not dependent on the current density …”
Section: Computational Methodologies To Model Electrocatalytic Enviro...mentioning
confidence: 99%
“…For example, the inclusion of applied potential and kinetics to the model developed by Exner showed that volcano plots describing the activity of electrocatalysts toward the HER shifted such that electrocatalysts with endergonic binding of hydrogen, as opposed to thermoneutral adsorption, are predicted to have optimal HER activity. 355 In another recent example, Dickens et al calculated electrochemical OER activation barriers and reaction energetics under an applied potential, resulting in an OER volcano plot that is a function of the current density, as opposed to thermodynamic, limiting-potential volcano plots that are not dependent on the current density. 356 In computational thermocatalytic studies, the calculation of activation barriers through DFT is well-established, with various methods including the climbing-image nudged elastic band (CI-NEB) 357 and dimer 358,359 methods.…”
Section: Computational Methodologies To Model Electrocatalytic Enviro...mentioning
confidence: 99%
“…The ΔG H* in the V Te site displays its biggest value above 0.6 eV, while the ΔG H* in the DV Te site exhibits a favorable value around 0.3 eV (Figure d) . Further analysis between ΔG H* and theoretical exchange current density i 0 indicates a “volcano” relationship (Figure e), revealing that the existence of three types of vacancies, including V Pd , V Te , and DV Te , will have the best optimized HER property for PdTe 2 . ,, …”
Section: Introductionmentioning
confidence: 99%